2022
DOI: 10.1200/po.22.00390
|View full text |Cite
|
Sign up to set email alerts
|

Rare FGFR Oncogenic Alterations in Sequenced Pediatric Solid and Brain Tumors Suggest FGFR Is a Relevant Molecular Target in Childhood Cancer

Abstract: PURPOSE Multiple FGFR inhibitors are currently in clinical trials enrolling adults with different solid tumors, while very few enroll pediatric patients. We determined the types and frequency of FGFR alterations ( FGFR1-4) in pediatric cancers to inform future clinical trial design. METHODS Tumors with FGFR alterations were identified from two large cohorts of pediatric solid tumors subjected to targeted DNA sequencing: The Dana-Farber/Boston Children's Profile Study (n = 888) and the multi-institution GAIN/iC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…28 In contrast, FGFR1-related fusions are rare in sarcomas and have mostly been described in central nervous system malignancies. [33][34][35] Thus, FGFR1::TACC1 fusion identified in case #2 has been a recurrent event in pediatric low-grade gliomas (pLGG), occurring in 2%-3% of cases, 36 further supporting its oncogenic nature. Moreover, clinical activity of an FGFR inhibitor has been reported in a pLGG patient with this fusion.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…28 In contrast, FGFR1-related fusions are rare in sarcomas and have mostly been described in central nervous system malignancies. [33][34][35] Thus, FGFR1::TACC1 fusion identified in case #2 has been a recurrent event in pediatric low-grade gliomas (pLGG), occurring in 2%-3% of cases, 36 further supporting its oncogenic nature. Moreover, clinical activity of an FGFR inhibitor has been reported in a pLGG patient with this fusion.…”
Section: Discussionmentioning
confidence: 93%
“…27 In addition, an FGFR1::EBF2 fusion was reported in an CD34-positive infantile spindle cell sarcoma, NOS, which responded to erdafitinib (a pan-FGFR inhibitor). 35 In RMS, FGFR alterations have been reported in 7-13% of cases, 3,4,47,48 mostly activating point mutations or/and amplifications and involving FGFR4. 3 FGFR1 overexpression in RMS was also described possibly related to hypomethylation of a CpG island upstream to FGFR1 exon 1 49 or to increased copy number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] A recent intensive study of pediatric solid tumors revealed FGFR1 alterations in a small proportion of non-CNS tumors. 12 Among eight sarcoma cases with the FGFR1 alteration, seven cases revealed FGFR1 amplification, while one case revealed FGFR1 structural variant. 12 Thus, to the best of our knowledge, our patient is the first reported case of FGFR1 TKDD-positive soft tissue tumor.…”
Section: Meanwhile Cancer Genome Profiling Of Her Tumor Specimen Withmentioning
confidence: 93%
“…12 Among eight sarcoma cases with the FGFR1 alteration, seven cases revealed FGFR1 amplification, while one case revealed FGFR1 structural variant. 12 Thus, to the best of our knowledge, our patient is the first reported case of FGFR1 TKDD-positive soft tissue tumor. There was no clinicopathological similarity between the present soft tissue tumor and FGFR1 TKDD-positive LGGs or DNTs, except that these tumors are not high-grade malignancies.…”
Section: Meanwhile Cancer Genome Profiling Of Her Tumor Specimen Withmentioning
confidence: 93%